Source model estimation of the 2005 Kyushu Earthquake, Japan using Modified Semi Empirical Technique. (1st October 2017) - Sandeep,; Joshi, A.; Sah, S.K.; Kumar, Parveen; Lal, Sohan; Vandana,; Kamal,; Singh, R.S.
Graphical abstract: Highlights: A source model with two SMGAs is estimated for the 2005 Kyushu earthquake (Mw 6.6). Modified semi empirical technique simulated the records for estimated rupture model. This confirms the validity of estimated source model with used MSET technique. Abstract: The 2005 Kyushu earthquake (MW 6.6, MJMA 7.0) occurred northwest of Fukuoka, Japan causing much damage and injuries. Here, we model the earthquake's source using the data recorded at surrounding field stations. Two isolated strong motion generation areas (SMGA) are identified on the rupture plane. The parameters of each SMGA are estimated using source displacement spectra and then used the spatiotemporal distribution of aftershocks to identify possible locations of SMGAs on the rupture plane. A modified semi empirical technique (MSET) simulated the records for the estimated rupture model. We then compared the observed and simulated acceleration records from eight regional stations. A comparable match between the observed and simulated records confirms the robustness of two SMGA rupture model and ability of MSET to simulate strong ground motion.